Prohibition of Concurrent Position of Commissioner of State-Owned Enterprises Reviewed Under Indonesian Business Competition Law - Geodewa, Darcyando (Program Doktor Ilmu Hukum, Universitas Krisnadwipayana, 2023)
One of the assessments of the dominant position of a business actor can be conducted based on the affiliation relationship of the business actor with other business actors, where the affiliation relationship regulated in Law of the Republic of Indonesia Number 5 Year 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition is concurrent positions and cross-shareholdings. Concurrent positions are prohibited when a person holds positions as directors or board of commissioners in two or more companies at the same time, where the companies are in the same relevant market, have close links in the type and/or field of business, or together can control the market share of certain services and/or goods. Legal issues regarding the concurrent position of members of the board of commissioners of BUMN arose during the enactment of Permen-BUMN PER-10/MBU/10/2020, which allows members of the board of commissioners of BUMN to hold concurrent positions under certain conditions. This is normative legal research that examines the prohibition of concurrent positions of BUMN commissioners in terms of business competition law in Indonesia.